2007
DOI: 10.1007/s10833-007-9053-7
|View full text |Cite
|
Sign up to set email alerts
|

Schools implementing Zero: The process of implementing an anti-bullying program in six Norwegian compulsory schools

Abstract: In 2002 the Prime Minister of Norway initiated a central Manifesto against bullying and invited all schools to participate in anti-bullying programs. Two programs were supported by the central authorities. This paper draws on a Norwegian project where six compulsory schools participated in one of those programs. Our focus was on the implementation process in the schools. We wanted to see how the schools' readiness for the program influenced the implementation. Group interviews with the project groups at the sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 23 publications
1
17
0
5
Order By: Relevance
“…Therefore, the conditions for continuation differed. This is in line with previous research suggesting that schools differ in how effective they are at school J Educ Change (2010) 11:323-344 337 improvement efforts (Hopkins et al 1997;Midthassel and Ertesvåg 2008;Stoll et al 2001). Given the results, the implementation during the first year and the continuation after the program period at the four schools can be characterized in three different ways: (1) hardly got off the starting block, (2) got started but faded, and (3) heading towards sustained improvement.…”
Section: Discussion and Final Thoughtsupporting
confidence: 90%
See 2 more Smart Citations
“…Therefore, the conditions for continuation differed. This is in line with previous research suggesting that schools differ in how effective they are at school J Educ Change (2010) 11:323-344 337 improvement efforts (Hopkins et al 1997;Midthassel and Ertesvåg 2008;Stoll et al 2001). Given the results, the implementation during the first year and the continuation after the program period at the four schools can be characterized in three different ways: (1) hardly got off the starting block, (2) got started but faded, and (3) heading towards sustained improvement.…”
Section: Discussion and Final Thoughtsupporting
confidence: 90%
“…Although they were able to implement some actions to prevent and reduce problem behavior, they were not able to increase the collective power to improve the school as an organization. Midthassel and Ertesvåg (2008) found that schools with weak traditions of school development programs struggled more in implementing the program than more experienced schools. Also, weak leadership from the management was a factor in the poor results.…”
Section: Discussion and Final Thoughtmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, studies have shown that the degree of principals' involvement in and attention to processes of change is decisive for the teachers' degree of commitment and motivation in these processes (e.g., Huberman & Miles, 1984). Whether principals are involved in the planning and leadership of change initiatives is also important for the quality of implementation (Midthassel & Ertesvåg, 2008). Finally, McLaughlin andTalbert (2001, 2006) found that teachers are in a strategic position to promote collaboration between teachers and that a large proportion of the differences between strong and weak professional communities in sixteen American high-schools could be explained by the role of leadership.…”
Section: School Leadershipmentioning
confidence: 99%
“…There may be a vast gap between written policies and their daily integration into the school's agenda (Glover et al 1998;Midthassel and Ertesvag 2008;Woods and Wolke 2003). It has been suggested that anti-bullying policies are not adequately monitored within schools (Glover et al 1998;Midthassel and Ertesvag 2008;Woods and Wolke 2003).…”
Section: Discussionmentioning
confidence: 99%